2021
DOI: 10.3389/fcell.2021.706129
|View full text |Cite
|
Sign up to set email alerts
|

Novel Markers in Pediatric Acute Lymphoid Leukemia: The Role of ADAM6 in B Cell Leukemia

Abstract: BackgroundThe extensive genetic heterogeneity found in the B cell precursor acute lymphoblastic leukemia (BCP-ALL) subtype of childhood ALL represents a potential repository of biomarkers. To explore this potential, we have carried out in silico analysis of publicly available ALL datasets to identify genetic biomarkers for childhood BCP-ALL, which could be used either individually or in combination as markers for early detection, risk stratification, and prognosis.MethodsTo explore novel genes that show promis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Low miR-574 expression seems to efficiently discriminate childhood T-ALL from B-ALL patients, whereas TLX1 -deregulated cases seem to be excluded from this pattern [ 79 , 165 ]. Notably, significantly higher levels of miR-574 have been found in BCP-ALL, KMT2A -r and TCF3 - PBX1 subtypes in comparison with other B-ALL cases [ 202 ].…”
Section: Resultsmentioning
confidence: 99%
“…Low miR-574 expression seems to efficiently discriminate childhood T-ALL from B-ALL patients, whereas TLX1 -deregulated cases seem to be excluded from this pattern [ 79 , 165 ]. Notably, significantly higher levels of miR-574 have been found in BCP-ALL, KMT2A -r and TCF3 - PBX1 subtypes in comparison with other B-ALL cases [ 202 ].…”
Section: Resultsmentioning
confidence: 99%
“…The highest result is achieved with a Decision Tree (DT) of 98%. In this article (Alsuwaidi et al, 2021 ), the author investigates novel genes demonstrating optimistic clinical and molecular signatures and uses a lymphoid cancer dataset. Lymphoblastic and lymphoid leukemia research comprising 1706 individuals and 2144 data are found in three different research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Acute lymphoblastic leukemia (ALL) is malignant transformation and uncontrolled proliferation of lymphoid hematopoietic progenitor cells, finally invading bone marrow and blood [ 1 , 2 ]. Although high cure rate can be achieved due to exist therapeutic regimens, subsequent chemotherapy resistance, disease relapse and poor prognosis remain a significant challenge [ 3 ].…”
Section: Introductionmentioning
confidence: 99%